PENGARUH METODE TALKING STICK TERHADAP HASIL BELAJAR FIKIH PADA SISWA KELAS VII SMP MUHAMMADIYAH 2 GATAK - Dzikri Khoirul Amin; Muhammad Jafar Nashir (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to determine how much the learning outcomes of seventh grade students in Jurisprudence subjects using the Talking Stick method, as well as to analyze the effect of the method on student learning outcomes at SMP Muhammadiyah 2 Gatak in the 2024/2025 school year. This research uses a descriptive quantitative approach. The sample was taken purposively in class VII A as many as 31 students. Data collection techniques included questionnaires, observations, and documentation, while data analysis was carried out using descriptive and inferential statistical tests with the help of SPSS 25. The results showed that the average value of student learning outcomes was 88.19, with a good category, where the highest score reached 98 and the lowest 80. Pearson Product Moment correlation analysis showed a positive and significant influence between the application of the Talking Stick method and learning outcomes, with a correlation value of 0.794 and a coefficient of determination of 0.630, which means that the Talking Stick method contributed 63% to improving Fikih learning outcomes. This finding proves that the Talking Stick method is able to increase active participation, speaking courage, and students' understanding of the Jurisprudence material. Thus, the application of this method is highly recommended as an innovative learning strategy to support the achievement of Islamic religious education goals that not only focus on cognitive aspects, but also strengthen students' character and spiritual values.